Optimal forwarding routing protocol in ipv6-based wireless sensor network - Jamil, Ansar (2009)
Wireless Sensor Networks (WSNs) is one of emerging technology nowadays. WSNs become very important and being used widely especially in embedded applications. Normally, these applications require numerous low cost, low power and low data sensor nodes that communicating over multiple hop to cover a large geographical area. Currently, a popular routing network protocol in WSNs is not compatible with IP-Based network _and can not provide Internet connection. It is because numerous sensor nodes is not practical for each one of them to be assigned with unique IP address due to limited IP address available in IPv4. Introduction of IPv6 will solve this issue. The objective of this research is to implement Optimal Forwarding routing protocol (OF) in IPv6-based WSNs and measure it performance in term of throughput. OF is one of routing protocol that can provides higher packet delivery ratio. The routing protocol will takes into account link quality, route cost and the receive signal strength of next hop sensor nodes in making routing decision in the network. In WSNs, TinyOS is the most widely used operating system. Thus, programming code of the OF routing protocol algorithm is written using NesC language, which is a high level programming language that emulates the syntax and functionality of hardware description languages, and provides components for communication, thread coordination, and hardware abstraction. Then, developed code is programmed into TelosB radio sensors boards in WSN test beds. TelosB consist of low power transceiver based on CC2420 ChipCon chips that employ IEEE 802.15.4 physical and MAC layers specifications. Here, actual performance of OF routing protocol is evaluated and compared with Greedy Forwarding and RIP routing protocol in WSN test bed. Later, OF routing protocol is implemented in temperature/humidity sensing application.